18th AIAA Non-Deterministic Approaches Conference 2016
DOI: 10.2514/6.2016-0433
|View full text |Cite
|
Sign up to set email alerts
|

Sparse polynomial surrogates for aerodynamic computations with random inputs

Abstract: This paper deals with some of the methodologies used to construct polynomial surrogate models based on generalized polynomial chaos (gPC) expansions for applications to uncertainty quantification (UQ) in aerodynamic computations. A core ingredient in gPC expansions is the choice of a dedicated sampling strategy, so as to define the most significant scenarios to be considered for the construction of such metamodels. A desirable feature of the proposed rules shall be their ability to handle several random inputs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Polynomial surrogates for aerodynamic computations have been outlined in e.g. [49]. We basically follow this presentation here.…”
Section: Polynomial Surrogatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Polynomial surrogates for aerodynamic computations have been outlined in e.g. [49]. We basically follow this presentation here.…”
Section: Polynomial Surrogatesmentioning
confidence: 99%
“…In [49] it has been observed that such sparse rules typically become competitive with respect to tensor grids for dimensions D ≥ 4. Consequently, collocation techniques with sparse quadratures or adaptive regression strategies have been developed in order to circumvent the dimensionality concern [5,28,64].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, one has z!:=normalΓfalse(z+1false)=0+tzetnormaldt and Γ( p + 1) = p !, the usual factorial, if p is an integer. Jacobi polynomials arise in gPC expansions for random variables following beta distributions of the first kind; see, e.g., . The normalization constant γ n in then reads γn=2α+β+1(n+α)!(n+β)!(2n+α+β+1)(n+α+β)!n!. The linearization coefficients B n ( j , k ) in the general linearization problem Jj(λ,δ)(x)Jk(μ,ν)(x)=n=|jk|j+kBn(j,k)Jn(α,β)(x),α,β,λ,δ,μ,ν>1, are given in [, equation (12)] in terms of double hypergeometric functions (the so‐called Kampé de Fériet functions).…”
Section: Higher‐order Moments Of Orthonormal Polynomialsmentioning
confidence: 99%
“…∶= Γ(z + 1) = ∫ +∞ 0 t z e −t dt and (p + 1) = p!, the usual factorial, if p is an integer. Jacobi polynomials arise in gPC expansions for random variables following beta distributions of the first kind; see, e.g., [3,13]. The normalization constant n in (3) then reads n = 2 + +1 (n + )!…”
Section: Jacobi Polynomialsmentioning
confidence: 99%
See 1 more Smart Citation